2020
DOI: 10.3390/jcm9123919
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroscopic Findings of Extra-Cervical Facet Joint Flow and Its Incidence on Cervical Facet Joint Arthrograms

Abstract: Cervical facet joint (CFJ) syndrome is a common cause of neck pain. For its diagnosis and treatment, CFJ injection with arthrogram is generally performed. This study aimed to investigate the frequency of extra-CFJ flow on CFJ arthrograms during injections and its differences according to age, sex, and cervical vertebral level. We analyzed 760 CFJ arthrograms administrated to 208 patients diagnosed with CFJ syndrome. Arthrograms at each vertebral level were collected to evaluate the normal CFJ and extra-CFJ flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
(35 reference statements)
1
7
0
Order By: Relevance
“…Its articular capsules are generally thin and loose, but they seem longer, looser, and thinner in the cervical region. 33 Although the previous RCT 6 and our study suggest that FJ steroid injection can be a valid and safe alternative to TFE steroid injection in patients with cervical radicular pain, FJ steroid injection may cause iatrogenic damage to the FJ capsule. 34 Therefore, incorporating the FJ steroid injection in patients with cervical radicular pain should be at the physician’s discretion.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Its articular capsules are generally thin and loose, but they seem longer, looser, and thinner in the cervical region. 33 Although the previous RCT 6 and our study suggest that FJ steroid injection can be a valid and safe alternative to TFE steroid injection in patients with cervical radicular pain, FJ steroid injection may cause iatrogenic damage to the FJ capsule. 34 Therefore, incorporating the FJ steroid injection in patients with cervical radicular pain should be at the physician’s discretion.…”
Section: Discussionmentioning
confidence: 51%
“…Kelekis et al 13 demonstrated an efficacious, feasible, and indirect cervical nerve root injection technique: puncture of the facet joint capsule with subsequent distribution of the corticosteroid intraarticularly, periradicularly, and within the epidural space. Won et al 33 mentioned that extra-FJ flow, including epidural leakage, showed high frequency at the lower cervical vertebrae, where there are many strains of capsular ligaments subject to peak FJ compression due to sliding.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have sought to determine the specificity of IA cervical facet injections. In an observational study examining the accuracy of 760 fluoroscopically-guided IA injections performed in 208 patients using 0.2 mL of contrast administered through a 25-gauge needle, Won et al [ 225 ] found that joint overflow occurred in 23.6% of injections, being highest at C5–6 (36.2%) and lowest at C3–4 (3.3%). In a retrospective study evaluating the spread patterns of 29 patients who underwent a single CT-fluoroscopy-guided cervical IA facet injection performed with 0.5–1 mL of contrast and 1 mL of steroid, Bureau et al [ 224 ] reported IA and retrodural spread in 62% of injections, IA and epidural spread in 7%, and extra-articular spread without IA contrast was observed in 21% of injections.…”
Section: Question 8: What Is the Ideal Volume For Prognostic Mbb And Ia Injections?mentioning
confidence: 99%
“…Moreover, the unprecedented development and progress in the management of pain, specifically utilizing these interventional techniques, heralded the evolution of interventional pain management cited by or through the Korean Journal of Pain (KJP). Of particular interest are researches that re-examine the anatomical structures that may be meaningful in relation to the cause of pain or its treatment [ 2 - 5 ].…”
mentioning
confidence: 99%
“…The authors, each with more than 20 years of experience in the field of pain medicine or human anatomy, discovered interesting facts in their conversation [ 4 ]. They found differences in the perceptions of the clinical significance of a particular anatomical structure, and came to the conclusion that these differences were more common than they had previously thought.…”
mentioning
confidence: 99%